Los bombardeos aéreos de poblaciones civiles en 1938: los límites de la independencia de la diplomacia vaticana con respecto a las políticas de Francia y el Reino Unido - Marquina, Antonio (UNISCI Discussion Papers, 2006)
The Vatican policy towards the two sides in the Spanish conflict was not simple. It may be even described as complicated. The complication was due to the structure of relations with the great powers at that time, which had peculiar relations with the two fighting sides and above all because of the extermination policy of everything religious – Catholic in the Republican zone. It must be noted that, from the diplomatic point of view, the good relations that the Vatican had with France and the United Kingdom, in comparison to the tense relations with the fascist countries, were a reason for a rapprochement to the Republican side. It must also be said that the Soviet Union was able to act in the conflict as long as the French-Britain non intervention policy was kept and an agreement between the United Kingdom and Italy on the Mediterranean was not reached.